2022
DOI: 10.3390/insects13080705
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic-Related Divergence in Perceiving Suitable Host Plants among Five Spider Mites Species (Acari: Tetranychidae)

Abstract: Spider mites belonging to the genus Tetranychus infest many important agricultural crops in both fields and greenhouses worldwide and are diversified in their host plant range. How spider mites perceive their suitable host plants remains not completely clear. Here, through two-host-choice designs (bean vs. tomato, and bean vs. eggplant), we tested the efficacies of the olfactory and gustatory systems of five spider mite species (T. urticae, T. truncatus, T. pueraricola, T. piercei, and T. evansi), which differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
3
0
0
Order By: Relevance
“…This result aligns with our previous finding that T. urticae is more sensitive than T. truncatus in perceiving suitable host plants (Hu et al. , 2022). Our previous study also found phylogenetically related divergence in perceiving suitable host plants among 5 spider mite species (Hu et al.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result aligns with our previous finding that T. urticae is more sensitive than T. truncatus in perceiving suitable host plants (Hu et al. , 2022). Our previous study also found phylogenetically related divergence in perceiving suitable host plants among 5 spider mite species (Hu et al.…”
Section: Discussionsupporting
confidence: 93%
“…This result aligns with our previous finding that T. urticae is more sensitive than T. truncatus in perceiving suitable host plants (Hu et al, 2022). Our previous study also found phylogenetically related divergence in perceiving suitable host plants among 5 spider mite species (Hu et al, 2022), suggesting an important role of chemoreception-related gene families in host-related divergence of taxa, which may lead to host-associated speciation. In other insects, chemoreception genes can be highly differentiated among host races, such as in the pea aphid, Acyrthosiphon pisum (Smadja et al, 2012).…”
Section: Gene Families Related To Chemoreceptionsupporting
confidence: 91%
See 1 more Smart Citation